PELATIHAN BUDIDAYA ALPUKAT DENGAN METODE SAMBUNG PUCUK KEPADA PETANI ALPUKAT DESA IWUL, BOGOR - Lischer, Kenny; Khayrani, Apriliana Cahya; Nurhayati, Retno Wahyu; Laksono, Auzan Luthfi; Izza, Nadira Nurul (Universitas Padjadjaran, 2024)
Avocado is one of the important commodities as food and as a source of nutrition worldwide. Previous research shows that avocado has antioxidants that benefit for health, such as vitamins A, C, and E, potassium, and unsaturated fat. So, avocados have various health activities such as preventing stroke, reducing cholesterol levels, skin moisturizers, and functional foods for babies. Therefore, a lot of people want to farm avocados by themselves. One of the groups of farmers with experience comes from Desa Iwul, Bogor. The avocado farm is one of their primary incomes. However, the activity is interrupted due to the planning of land construction. Groups of farmers from Desa Iwul, Bogor might face loss of their sources of income. To overcome this problem, groups of community development from Bioprocess Engineering, Faculty of Engineering Universitas Indonesia tried to transfer knowledge about avocado cultivation techniques using grafting methods. The activities were done for 2 months as a form of training for trainers of selected avocado farmers and training from trained avocado farmers to other avocado farmers and society. The results show that the grafting method has successfully been done not only by trained avocado farmers but to untrained avocado farmers and society. By this activity, the success rate of the grafting method has been increased.Avocado is one of the important commodities as food and as a source of nutrition worldwide. Previous research shows that avocado has antioxidants that benefit for health, such as vitamins A, C, and E, potassium, and unsaturated fat. So, avocados have various health activities such as preventing stroke, reducing cholesterol levels, skin moisturizers, and functional foods for babies. Therefore, a lot of people want to farm avocados by themselves. One of the groups of farmers with experience comes from Desa Iwul, Bogor. The avocado farm is one of their primary incomes. However, the activity is interrupted due to the planning of land construction. Groups of farmers from Desa Iwul, Bogor might face loss of their sources of income. To overcome this problem, groups of community development from Bioprocess Engineering, Faculty of Engineering Universitas Indonesia tried to transfer knowledge about avocado cultivation techniques using grafting methods. The activities were done for 2 months as a form of training for trainers of selected avocado farmers and training from trained avocado farmers to other avocado farmers and society. The results show that the grafting method has successfully been done not only by trained avocado farmers but to untrained avocado farmers and society. By this activity, the success rate of the grafting method has been increased.